MedSMA℞T Adventures in PharmaCity Game: Youth Experiences and Recommendation for Use in Opioid Safety Education - Olufunmilola Abraham; Courtney R. Koeberl; Tyler J. McCarthy (MDPI AG, 2023)
Adolescents are often excluded from the creation of opioid safety interventions; therefore, it is crucial to design evidence-based interventions tailored for and with youth. Video games are ubiquitous and approachable to adolescents making them an accessible educational modality. MedSMA℞T: Adventures in PharmaCity is a serious game that educates adolescents and their families on the safe, appropriate, and responsible use of opioid prescriptions. The first objective of the study was to elucidate adolescents' experiences and perceptions of the game. The second objective was to elicit their recommendations for use and suggestions for improvement. Adolescents were recruited through Qualtrics research panels, social media, listservs, and snowball sampling. Recruitment occurred between April 2021 and October 2021. Eligible adolescents played the game and completed a follow-up virtual semi-structured interview with a study team member. Interviews were transcribed verbatim and uploaded to NVivo for data analysis. A thematic content analysis was performed. A total of seventy-two adolescents participated. Analysis yielded four themes: prior gaming experience, educational salience, game design impressions, and recommendations for improvement. Most adolescents approached MedSMA℞T with prior gaming experience. The youth correctly identified the game's intended objective: the promotion of opioid medication safety. Adolescents had overarchingly positive impressions of the game's levels, characters, and graphics. Study participants suggested expanded game levels, improved controls, and more instructions for gameplay. In summary, adolescents had favorable experiences using the MedSMA℞T game which allude to the wide-spread acceptability of this intervention among young people.